Pengaruh pembelajaran daring di masa pandemi Covid-19 terhadap hubungan interpersonal pada mahasiswa - Richardus Rizky Saunoah; Katharina Edeltrudis Perada Korohama (Universitas Indraprasta PGRI, 2022)
this study aims to determine the effect of online learning during the covid-19 pandemic on interpersonal relationships at Nusa Cendana University students. This study uses a quantitative approach to the method of distributing instrument questionnaires. University students of Nusa Cendana have been previously interviewed regarding interpersonal relationships during the Covid-19 pandemic. The sample in this study were 68 respondents using the proportional stratified random sampling technique. The data analysis technique was carried out using a simple linear regression technique. Based on the results of the data obtained, it is concluded that online learning during the covid-19 pandemic has an effect on interpersonal relationships. This can be seen from the R Square value of 0.520 which means that online learning during the covid-19 pandemic contributed 52% to interpersonal relationships and the rest was influenced by other factors.